The Meaning of Mangolusi in The Batak Toba Wedding Ritual - Siregar, Tiarnita Maria Sarjani Br; Azzahra, Ivana Rasikah; Siregar, Nur Aini; Karosekali, Yoga Marchell; Salim, Zuraima Fitriani (Mutiara: Multidiciplinary Scientifict Journal, 2024)
This study explores how the meaning of Mangulosi in the traditional wedding rituals of the Batak Toba people is deeply explored and uses ethnographic communication theory to present the wedding customs of the Toba Batak people. (Hymes in Kuswarno 2008: 22) and the constructivist paradigm. Data collection techniques were conducted through in-depth interviews, non-participant observation, documentation, literature review, combination/triangulation and sources. The researcher used the traditional Toba Batak marriage subject, namely Mangulosi, as a data source to analyze the series of questions asked in the study with reference to the theory used. Research findings show that the traditional marriage landscape is in disarray. Toba Batak is a sacred custom that all members of the Toba Batak community perform or must perform, both at the time of marriage and after death. As for , the event begins with a marriage proposal from the groom's family (first her ) to the bride's family. Traditional Wedding the Mangulosi event at Batak Toba begins with a marriage proposal from the groom's family to a woman from the bride's family. Thereafter, the wedding continued as a regular wedding until the end of Event. Regarding weddings, there is a gift piece Uros Cross given by the groom to the bride. This matter is a symbol of love for a life partner, and also has other meanings, namely, getting acquainted with or uniting with a formal family that takes care of the marriage. The event will then conclude with 4,444 pieces of food distributed to other people and the surrounding community. This is part of the traditional Toba Batak wedding ceremony. Traditional Batak Wedding the act of mangulosi in Toba is performed and symbolized by the gift of uros cloth from the male family to the female family. This is part of the traditional Batak wedding ceremony of Toba Mangulosi and has the significance of ritual sanctity, obligatory wedding ceremony, and symbol of love between the groom and bride women.